R-process enrichment in ultrafaint dwarf galaxies. Issue 1 (14th March 2020) - Tarumi, Yuta; Yoshida, Naoki; Inoue, Shigeki
ABSTRACT: We study the enrichment and mixing of r-process elements in ultrafaint dwarf galaxies (UFDs). We assume that r-process elements are produced by neutron-star mergers (NSMs), and examine multiple models with different natal kick velocities and explosion energies. To this end, we perform cosmological simulations of galaxy formation to follow mixing of the dispersed r-process elements driven by star formation and the associated stellar feedback in progenitors of UFDs. We show that the observed europium abundance in Reticulum II is reproduced by our inner explosion model where an NSM is triggered at the centre of the galaxy, whereas the relatively low abundance in Tucana III is reproduced if an NSM occurs near the virial radius of the progenitor galaxy. The latter case is realized only if the neutron-star binary has a large natal kick velocity and travels over a long distance of a kiloparsec before merger. In both the inner and outer explosion cases, it is necessary for the progenitor galaxy to sustain prolonged star formation over a few hundred million years after the NSM, so that the dispersed r-process elements are well mixed within the interstellar medium. Short-duration star formation results in inefficient mixing, and then a large variation is imprinted in the stellar europium abundances, which is inconsistent with the observations of Reticulum II and Tucana III.